PENGENDALIAN BANJIR SISTEM BENDUNG PUCANG GADING – DOMBO SAYUNG SEMARANG - Rr. Ayu Khrisina Maharani; Septian Dwi Wicaksono; Suharyanto Suharyanto; Robert J. Kodoatie (Jurnal Karya Teknik Sipil, 2013)
Flood is one of the occasion that quite often happens in Semarang City. Dombo-Sayung is being one of the areas which flood is often happened there. Flood give many negative impacts that can’t be ignored, for example is cause damage to infrastructur: buildings, houses, and roads. And even stop the mobility in that area if the flood is happened for a long time. The purpose of Flood Control of Pucang Gading Weir System-Dombo Sayung, Semarang is to minimize or even avoid the flood happened in Dombo-Sayung Area by designing the flood control system which can overcome the flood problem. The method that used for Flood Control of Pucang Gading Weir System-Dombo Sayung Semarang are primary and secondary data collection, hydrology analysis such as flood’s hydrograph, hydraulics analysis for planning the dimension of retention pond and dimention of river improvement Dombo-Sayung Channels. Flood Control of Pucang Gading Weir System- Dombo sayung give result to using retention pond with the size is (300x190x7) m³ for run off volume channels is 334.691,643 m³ and  dimension of river improvement Dombo Sayung Channels becoming (35x6) m2 for the the income flow is 300 m³.